Hambatan dan Peluang Efektivitas Alternative Dispute Resolution (ADR) dalam Penyelesaian Sengketa Bisnis di Indonesia Berdasarkan Undang-Undang Nomor 30 Tahun 1999 - Frensiska Ardhiyaningrum; Diana Setiawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Business disputes are increasing in Indonesia along with the growth of economic relationships. Litigation is often perceived as time-consuming and costly, making Alternative Dispute Resolution (ADR) a more efficient and relationship-friendly alternative. This study aims to analyze the obstacles and opportunities in implementing ADR for business dispute resolution in Indonesia, based on the legal framework provided by Law Number 30 of 1999. The research employs a normative legal approach with descriptive analysis. Data were collected through literature reviews of legal regulations, academic literature, and journal articles. The findings reveal that although ADR holds significant potential for resolving business disputes efficiently and cost-effectively, its implementation faces several challenges. The primary obstacles include the lack of awareness among business actors about ADR's benefits, the perception that ADR lacks the legal authority compared to litigation, and the limited quality of mediators and arbitrators. The study also highlights the importance of enhancing the capacity of ADR practitioners through continuous training and educating business actors to build trust in this method. By addressing these challenges, ADR is expected to become the primary choice for resolving business disputes, fostering a conducive business environment, and supporting long-term economic growth in Indonesia.